From Tradition to Competition: The Negosiation Process of Cultural Identity in Traditional Dancesport Choreography at National Competitions - Aligra Umaldi, Adrin Shiera; Sasanadjati, Jajuk Dwi; Hariyanto, Moh.; Sugito, Bambang; Sadhana, Senyum (GETER : Jurnal Seni Drama, Tari dan Musik, 2026)
Traditional dance performances in traditional dancesport competitions present a fundamental tension between efforts to preserve cultural identity and the need for sport standardization. This study aims to examine how coaches and athletes negotiate traditional cultural values ​​with technical-competitive requirements in the process of choreography creation. Using a qualitative, case study-based approach, this study analyzes three cases of national choreographers who created traditional numbers for the 18-25 year old dancesport category. Data were collected through semi-structured interviews, performance observations, and analysis of video documentation of practice sessions over a six-month period. Data analysis was conducted thematically using the theoretical frameworks of cultural hybridity (Bhabha) and embodiment (Csordas). The findings reveal three negotiation strategies used: (1) structural adjustments in the form of simplification of complex movement patterns; (2) expressive modifications through adjustments in energy intensity and tempo; and (3) semiotic restructuring while maintaining certain elements of cultural identification. This research has implications for the development of an assessment framework that is more sensitive to cultural authenticity in dancesport competitions and provides practical recommendations for choreographers in creating choreographies that meet competitive criteria while maintaining cultural values.